Flight dynamics and control modelling of damaged asymmetric aircraft - Ogunwa, T. T.; Abdullah, Ermira Junita (Institute of Physics Publishing, 2016)
This research investigates the use of a Linear Quadratic Regulator (LQR) controller to assist commercial Boeing 747-200 aircraft regains its stability in the event of damage. Damages cause an aircraft to become asymmetric and in the case of damage to a fraction (33%) of its left wing or complete loss of its vertical stabilizer, the loss of stability may lead to a fatal crash. In this study, aircraft models for the two damage scenarios previously mentioned are constructed using stability derivatives. LQR controller is used as a direct adaptive control design technique for the observable and controllable system. Dynamic stability analysis is conducted in the time domain for all systems in this study.